The linkage between team communication, team motivation and search and rescue team performance - Ahmad Zawawi, Azlyn; Ab Halim, Norsyazwani; Kamarunzaman, Nur Zafifa; Ahmad Zawawi, Azita; Halim, Fatimah Wati (AOSIS, 2023)
Orientation: This study examined the linkage between team communication, team motivation and search and rescue (SAR) team performance. Research purpose: The study intends to investigate the impact of selected team factors that affect team performance, while adding to the scarce studies done on SAR team performance (especially in Malaysia). Motivation for the study: Search and rescue teams are skilled elite teams that can reflect the true characteristics of a team’s performance. Research approach / design and method: The study comprised 850 individual team members who were aggregated into 209 teams. Teams were among the SAR teams of the Malaysian Fire and Rescue Department. The study used a quantitative approach, employing the purposive sampling technique. The relationships between team communication, team motivation and SAR team performance were analysed using the structural equation modelling (SEM). Main findings: The results indicate that team communication affects SAR team performance; however, the relationship is not mediated by team motivation. Practical/managerial implications: Team communication is vital to the achievement of teams’ objectives. However, in life-and-death situations, which are usual for SAR teams, team motivation does not have a role in how communication affects the teams’ performance. Team leaders and the managers of SAR teams need to focus on effective communication techniques in order to achieve excellent performance. This includes the use of appropriate verbal and non-verbal communication. Contribution/value-add: This study adds value to the current literature on team performance, specifically SAR team performance.